NLRP3/Caspase-1-Mediated Pyroptosis of Astrocytes Induced by Antipsychotics Is Inhibited by a Histamine H1 Receptor-Selective Agonist - He, Meng; Fan, Jun; Zhou, Ruqin; Gao, Guanbin; Li, Ruoxi; Zuo, YuFeng; Li, Benben; Li, Yanmei; Sun, Taolei (Frontiers in Aging Neuroscience, 2022)
Emerging data indicate that antipsychotic treatment causes brain volume loss and astrocyte death, but the mechanisms remain elusive. Pyroptosis, inflammatory cell death characterized by the formation of inflammatory bodies, increased expression of nod-like receptor proteins (NLRPs) such as NLRP3, and activation of caspases and gasdermin D (GSDMD) are largely associated with innate immunity, inflammation, and cell injury/death. However, the main effect of antipsychotics on astrocyte pyroptotic signaling and the molecular mechanisms remain obscure. In the present study, 72-h treatment with olanzapine, quetiapine, risperidone, or haloperidol significantly decreased the viability of astrocytes. Twenty-four hour treatment with olanzapine, quetiapine, risperidone, or haloperidol dose-dependently increased the protein expression of astrocytic NLRP3, NLRP6, caspase-1, caspase-4, and GSDMD. Co-treatment with a histamine H1 receptor agonist, 2-(3-trifluoromethylphenyl) histamine (FMPH), dose-dependently reduced the increased expression of NLRP3, caspase-1 and GSDMD induced by olanzapine, quetiapine, risperidone, or haloperidol. Moreover, olanzapine, quetiapine, risperidone, or haloperidol treatment induced pore formation in the membranes of astrocytes, and these effects were inhibited by FMPH co-treatment. Taken together, antipsychotic treatment activated astrocyte pyroptotic signaling, and these effects may be related to antipsychotic-induced astrocyte death. H1 receptor activation is an effective treatment strategy to suppress antipsychotic-induced astrocyte pyroptosis and inflammation.